(x + 1)(3x + 5)
Chat with our AI personalities
x2+8x = -3x2+5 4x2+8x-5 = 0 (2x+5)(2x-1) = 0 x = -5/2 or x = 1/2
If you mean: 3x2+8+5 = 0 Then it crosses the x axis at points -1 and -5/3
Assuming the 2 is meant to be a square this is the form: x2 - 3x2 = -2x2 + 8x + 5
x2 + 8x + 15 = (x + 3) (x + 5).
If you notice, 8x + 4 = 4(2x + 1), but there is an odd coefficient for x2, so there is guaranteed to be some remainder (that is 8x + 4 is not a factor of the polynomial): (24x3 - 5x2 - 48x - 8) ÷ (8x + 4) = 3x2 - 2x - 5 - (x2 - 12)/(8x + 4)